Economic Policy Positions of Austrian Parties in Historical Course: The Impact of Neoliberalism in Austrian Party Manifestos - Grimm, Christian (Momentum Quarterly, 2018)
Focus of this article is to analyse manifestos from Austrian parties concerning the historical neoliberal hegemony. The central aim is to detect how far content-related changes in party manifestos were effected by the neoliberal turn in the late nineteen seventies. Therefore an empirical longitudinal analysis was conducted, in which the currently manifestos were compared with those, who were not ascribed to the neoliberal age. The results show an increased impact of neoliberal contents in all current political programmes.
Keywords: Austrian Party Manifestos; Liberal Principles; Neoliberalism; Performativity of Economics